ANALISIS POTENSI DAN KARAKTERISTIK LIMBAH PADAT FLY ASH DAN BOTTOM ASH HASIL DARI PEMBAKARAN BATUBARA PADA PEMBANGKIT LISTRIK TENAGA UAP (PLTU) PT. SEMEN TONASA - Yunita, Eka; Rahmaniah, Rahmaniah; Fitriyanti, Fitriyanti (Universitas Islam Negeri Alauddin Makassar, 2017)
A research was conducted at Steam Power Plant (PLTU) of PT. Semen Tonasa in which the coal burning resulting waste that is dust, fly ash and bottom ash. This research aimed to find out how much solid waste was resulted and how was the characteristic. Based on the secondary data obtained, it was found out that this Steam Power Plant results 96,07 ton of fly ash dan 41,62 ton of bottom ash in a day. Then a test was conducted in laboratory with elemental content analysis method using XRF showing that the highest element was silica and iron while as the calculation result of LOI content, it was found that fly ash had low content of carbon so that it is good to use as mixture of cement. Meanwhile, bottom ash contained high content of carbon so that it is fit to apply with polymer materials. Furthermore, the analysis was continued using XRD method and found that fly ash BTG I was dominated with Davyne mineral phasa with hexagonal crystal structure. Bottom ash showed bavenite phasa with orthorhombic crystal structure. Meanwhile, at BTG 2, fly ash showed Quartz phasa with trigonal crystal structure (hexagonal axes) and for bottom ash, there was Berlinite phasa with trigonal crystal structure (hexagonal axes) and Gillespite phasa with yang orthorhombic crystal structure.Â Key Word: PLTU, Fly Ash, Bottom Ash, LOI, XRF, XRD